Legal Protection of Doctors in the Handling of Medical Emergencies - Ni Luh Gede Astariyani; Julio de Araujo da Silva (Contrarius, 2025)
The legal relationship between doctors and patients in medical emergency situations gives rise to complex consequences in terms of professional liability. In practice, doctors who have complied with professional standards and established operational procedures frequently face civil, criminal, or disciplinary claims when treatment outcomes fail to meet patients’ or their families’ expectations. This condition reflects the fragility of legal protection for doctors in Indonesia, as existing regulations have not yet been constructed upon a substantive conception of justice. This study aims to examine the underlying causes of the absence of just legal protection for doctors, to identify weaknesses in the substance, structure, and legal culture of health law, and to formulate a reconstruction of legal norms based on the value of dignified justice. Using a qualitative research design, this study employs a doctrinal (normative) legal research method through statutory analysis and a review of health law doctrines and relevant legal literature. The findings reveal that, first, the legal framework governing medical emergency services in Indonesia remains insufficiently grounded in justice-based values, resulting in normative ambiguity and disproportionate legal exposure for doctors acting in good faith and in accordance with professional standards. Second, overlapping authority among ethical, disciplinary, and criminal law institutions generates structural weaknesses that create legal uncertainty and subject doctors to multiple accountability mechanisms for a single medical action. Third, the prevailing legal culture tends to equate adverse medical outcomes with malpractice, rather than recognizing inherent medical risks and emergency constraints, thereby reinforcing a punitive orientation toward medical professionals. This study concludes that regulatory reconstruction grounded in the value of dignified justice is necessary to ensure proportional and fair legal protection for doctors in medical emergency services.